EFEKTIVITAS PENGGUNAAN AUGMENTED REALITY (AR) DALAM MENINGKATKAN PERUBAHAN ENERGI PADA SISWA KELAS 4 di SDN KARANGDUAK 2 - Adelia Carera; Holifa Kurniayati; Ihwan Ansyori; Masitoh Bunga Ayu Seruni (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the effectiveness of Augmented Reality (AR) in improving the understanding of energy transformation concepts among fourth-grade students at SDN Karangduak 2. Using a quasi-experimental design, the results indicate that the experimental group utilizing AR achieved significantly higher post-test scores compared to the control group. AR’s interactive visualization aids students in comprehending abstract concepts such as kinetic and potential energy while also enhancing learning motivation. This study confirms that AR is an innovative and effective instructional medium for improving science learning outcomes in elementary schools.